Sea-ice reconstructions from bromine and iodine in ice cores - Vallelonga, Paul; Maffezzoli, Niccolò; Saiz-Lopez, Alfonso; Scoto, Federico; Kjær, Helle Astrid; Spolaor, Andrea (Quaternary Science Reviews, 2021)
As the intricacies of paleoclimate dynamics are explored, it is becoming understood that sea-ice variability can instigate, or contribute to, climate change instabilities commonly described as “tipping points”. Compared to ice sheets and circulating ocean currents, sea-ice is ephemeral and continental-scale changes to sea ice cover occur seasonally. Sea-ice greatly influences polar albedo, atmosphere-ocean gas exchange and vertical mixing of polar ocean masses. Major changes in sea ice distribution and thickness have been invoked as drivers of deglaciations as well as stadial climate variability described in Greenland climate records as “Dansgaard-Oeschger” cycles and described in Antarctic climate records as “Antarctic Isotopic Maxima”. The role of halogens in polar atmospheric chemistry has been studied intensively over the past few decades. This research has been driven by the role of bromine, primarily as gas-phase bromine monoxide (BrO), which exerts a key control on polar tropospheric ozone concentrations. Initial findings led to the discovery of boundary-layer self-catalyzing heterogeneous bromine reactions fed by sunlight and ozone, known as bromine explosions. First-year sea-ice and blowing snow have been identified as key components for this heterogeneous bromine recycling in the polar boundary layer. This understanding of polar halogen chemistry – supported by an expanding body of observations and modeling – has formed the basis for investigating quantitative links between halogen concentrations in the polar atmospheric boundary layer and sea-ice presence and/or extent. Despite the clear importance of sea-ice in paleoclimate research, the ice core community lacks a conservative and quantitative proxy for sea-ice extent. The most commonly applied proxy, methanesulphonic acid (MSA), is volatile and has not been demonstrated reliably for ice core records extending beyond the last few centuries. Sodium has also been applied to reconstruct sea-ice extent in a semi-quantitative manner although the effects ...